THE ANALYSIS OF TAHFIDZ AL-QUR’AN LEARNING USING THE FLIPPED CLASSROOM METHOD : CREATING TEACHER-PARENT COLLABORATION - Umi Muntafi’ah; Alaika M Bagus Kurnia PS; Amelia Khoirunisa; Erviana Iradah Ulya (EDURELIGIA: Jurnal Pendidikan Agama Islam, 2024)
This study aimed to analyze in more depth how tahfidz is taught in class with the flipped classroom method. This study uses a case study method, with observation and interview data collection techniques. The results of this study, the tahfidz program at SMP Khadijah has not been implemented perfectly using the flipped classroom method. With notes, reactivating the tahfidz guidebook as educational communication to parents and guardians of students; implementing collaborative mentoring in muroja'ah both at home and in class; There needs to be concern from parents and guardians of students to control the development of students' memorization of the Al-Qur'an. So there needs to be a flipped classroom method with parents as one of the means of successful tahfidz learning. Learning to memorize the Qur'an in schools as an actualization of formal education, as well as family education can function as informal education, in addition the connecting media is the student's tahfidz guidebook which is shown to teachers and parents of students.